Vendor Hygienic Practices and Consumer Perception of Food Safety during the Carnival festival on the island of Tobago, West Indies. (March 2015) - Franklyn, Sherrae; Badrie, Neela
Abstract Local festivals are usually the highlights on the small island, Tobago, West Indies. The street vendors capitalized on the Carnival season where they provide a variety of foods and beverages on‐demand for masqueraders and spectators. Therefore, this study examined food safety and hygienic practices by vendors and consumer perception of such practices at the Carnival festivals in Tobago. Standard structured questionnaires and observational checklists were compiled and administered to 50 vendors and 150 consumers at five Carnival events. Each vendor was observed for frequency of practices for 15–20 min. Consumers were sampled systematically (every fifth person encountered) at each event. The vendors examined were generally female (70.0%), 41–50 years old (34.0%), possessed less than primary education (36.0%), acquired more than 5 years of experience (44.0%) and were stationary (78.0%). The most common food prepared and sold was hot dog (36.0% of all sold foods). Educated vendors practised good personal hygiene and on‐site food handling, whereas the others performed improper practices such as absence of aprons and hair covering, wearing of jewellery and handling money while serving. Also, vendors displaying valid food badges generally practised more proper personal hygiene and food handling than those without badges. The majority of the consumers examined were residents of Tobago (80.0%), female (74.7%), 21–30 years old (39.3%) and possessed secondary education (53.3%). More than half of the consumers purchased foods at Carnival events (57.3%). Most (82.7%) who did not purchase stored foods in coolers. More than half (58.0%) had seen or read Carnival food safety articles in the local newspapers and most (96.0%) were aware that illnesses can be transmitted via consumption of food. Additionally, 42 out of 74 respondents (56.8%), who indicated that they were affected by foodborne illness, sought medical help when foodborne illness was suspected. However, a mere 13 out of 74 consumers (17.6%), who indicated that they were affected by foodborne illness, lodged reports of suspected foodborne illness with the local health authority. Younger consumers (21–30 years old) mostly read food safety articles and were conscious of illness being transmitted via consumption of food. In addition, the more educated consumers (tertiary education) indicated awareness as well as formal reporting of foodborne illness. Some gaps in vendor practices included handling of money while serving (78.0%), failure to clean utensils (68.0%) and access to water (48.0%). Noteworthy, only visual observation and interviews were utilized in the study.